Randomized study of granulocyte colony stimulating factor for childhood B-cell non-Hodgkin lymphoma: a report from the Japanese pediatric leukemia/lymphoma study group B-NHL03 study. Issue 7 (2nd July 2016) - Tsurusawa, Masahito; Watanabe, Tomoyuki; Gosho, Masahiko; Mori, Tetsuya; Mitsui, Tetsuo; Sunami, Shosuke; Kobayashi, Ryoji; Fukano, Reiji; Tanaka, Fumiko; Fujita, Naoto; Inada, Hiroko; Sekimizu, Masahiro; et al.
Abstract: The objective of this study was to assess the impact of the primary prophylaxis of granulocyte colony-stimulating factor (G-CSF) in the management of childhood B-cell non-Hodgkin lymphoma (B-NHL). Patients with advanced-stage mature B-NHL were randomized to receive prophylactic G-CSF (G-CSF+) or not receive G-CSF (G-CSF−) based on protocols of the B-NHL03 study. The G-CSF group received 5 μg/kg/d Lenograstim from day 2 after each course of six chemotherapy courses. Fifty-eight patients were assessable, 29 G-CSF + and 29 G-CSF−. G-CSF + patients showed a positive impact on the meantime to neutrophil recovery and hospital stay. On the other hand, they had no impact in the incidences of febrile neutropenia, serious infections, stomatitis and total cost. Our study showed that administration of prophylactic G-CSF through all six chemotherapy courses for childhood B-NHL showed no clinical and economic benefits for the management of childhood B-NHL treatment.